2020
DOI: 10.3846/aviation.2019.11847
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mental Workload of Flight Attendants Based on Flight Duration: An Effort to Provide Safe Working Condition

Abstract: Flight attendants play a crucial role in the service of the airline industry. The aim of this present study is to examine the mental workload of flight attendants, and it possible relation to the flight duration. Two hundred and one Indonesian flight attendants participate voluntarily in this study by filling out a mental workload questionnaire, the NASA-TLX questionnaire, in the end of their flight schedule. Results show that the mental workload of flight attendants regardless the flight duration is on a rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In a cross-sectional study by Hu et al [ 17 ] of cabin crew, purser, and cabin manager, the authors confirmed that exhaustion from work, emotional distress, and insomnia were risk factors for decreased work ability. However, in a cross-sectional study of flight attendants conducted by Widyanti and Firdaus [ 18 ], a moderate mental workload was noted, regardless of flight duration. Lastly, Agampodi et al [ 19 ], in a cross-sectional study of flight attendants, found that females (the predominant gender in this role), low weight (under 56 kg), and shorter work experience (<7 years) were risk factors for injuries on board ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a cross-sectional study by Hu et al [ 17 ] of cabin crew, purser, and cabin manager, the authors confirmed that exhaustion from work, emotional distress, and insomnia were risk factors for decreased work ability. However, in a cross-sectional study of flight attendants conducted by Widyanti and Firdaus [ 18 ], a moderate mental workload was noted, regardless of flight duration. Lastly, Agampodi et al [ 19 ], in a cross-sectional study of flight attendants, found that females (the predominant gender in this role), low weight (under 56 kg), and shorter work experience (<7 years) were risk factors for injuries on board ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the ranking between below 35 years old and less than ten years' seniority, and between older than 36 years old and more than eleven years' seniority, results are also showed similar between age and seniority in the study. Widyanti and Firdaus (2019) studied on the mental workload of flight attendants and results also indicated that age and work experience didn't have significant differences on the mental workload of the flight attendants. Thus, it might be able to use one of age or seniority to be a variable in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The causes of fatigue risk of short-haul flights include scheduling early in the morning or late at night, early duty reporting time, frequent taking off and landing, multiple flight routes in a day, high-density airspace, consecutive shifts over several days, and many days on duty (IATA, ICAO, IFALPA, 2011;Roach et al, 2012). Widyanti and Firdaus (2019) collected the complained factors of flight attendants were included duration of rest period, jet lag, scheduling, duration of work and management such as management support which related with company planning.…”
Section: Factors In Company Planningmentioning
confidence: 99%
“…The workload of the flight attendants falls into the categories of physical and psychosocial workload, cabin crew workload is handling carry-on baggage, handling carts (beverage, meal, and duty-free), service to passengers, and safety checks. It should be underlined, however, that flight attendants also have to perform mentally demanding work such as safety and security checks [12]. This work is carried out by cabin crew within a limited time, especially on short and medium flights.…”
Section: Introductionmentioning
confidence: 99%